Highly efficient potassium fertilizer production by using a gemini surfactant. Issue 6 (22nd February 2019) - Huang, Zhiqiang; Cheng, Chen; Liu, Zuwen; Feng, Bo; Hu, Yajing; Luo, Wuhui; He, Guichun; Yu, Xinyang; Fu, Weng
Abstract : A gemini surfactant as a collector for froth flotation separation of KCl from NaCl to produce potassium fertilizer. Abstract : Herein, we report that a gemini surfactant can efficiently separate KCl from NaCl by froth flotation to produce potassium fertilizer (KCl). For achieving the obviously superior flotation performance (KCl recovery increased by 14.51%), the dosage of the gemini surfactant should be three times less than that of the conventional monomeric surfactant. Its unique properties, such as double active centers to mineral surfaces, double hydrophobic groups, and stronger surface tension reducing ability, make it a superior flotation collector for separation of KCl from NaCl in potassium fertilizer production.